Nodular-like glomerular lesion after long-standing chronic renal infection in a patient with medullary sponge kidney and mild hyperglycemia. (28th September 2022) - Nakashima, Saki; Kawada, Masahiro; Sekine, Akinari; Yamanouchi, Masayuki; Ikuma, Daisuke; Mizuno, Hiroki; Oba, Yuki; Hasegawa, Eiko; Suwabe, Tatsuya; Kono, Kei; Kinowaki, Keiichi; Ohashi, Kenichi; et al.
Abstract : A 63-year-old Japanese woman was admitted to our institute for the evaluation of proteinuria. The patient was diagnosed with medullary sponge kidney, distal type renal tubular acidosis, and renal infection at the age of 37. Thereafter, the patient had repeated renal infections. Urinary proteinuria appeared at around the age of 61 and gradually increased up to 1.0 g daily. In the same period, glycated hemoglobin (HbA1c) increased to 7.0%. On kidney biopsy, light microscopy showed a nodular glomerular lesion and capsular drop. Linear staining for immunoglobulin G along the glomerular basement membrane was observed by immunofluorescence. Electron microscopy showed thickening of the glomerular basement membrane to a width of 800–900 nm. A class III glomerular lesion was diagnosed according to the Tervaert classification. This case indicates that mild but prolonged hyperglycemia for more than 10 years may also contribute to the formation of nodular lesions, although long-standing repeated chronic renal infection and chronic acidosis may have been a precipitating factor in the formation of diabetic nephropathy, including nodular glomerular lesions. This hypothesis is of interest because nodular lesions specific to diabetes are currently considered to be associated with long-term severe hyperglycemia. Learning points: Nodular glomerular lesions in diabetes mellitus are thought to be associated with long-term severe hyperglycemia. This case shows that although mild, long-term hyperglycemia for more than 10 years may also contribute to the formation of nodular lesions and that repeated chronic kidney infections over the years and chronic acidosis may be facilitating factors in the formation of diabetic nephropathy, including nodular glomerular lesions. This case appears to be idiopathic nodular glomerulosclerosis of the medullary sponge kidney associated with chronic urinary tract infection.